The durability study of blend cement using sewage sludge ash (SSA) and eggshell - Lukman Syarif, Andi Lantara (2017)
During past recent years, Malaysia’s construction sector keep growing thus directly led to the increasing demand of construction material including cement. The increase in demand for the construction materials has called for an alternative way to develop or derive construction materials from other sources. Eggshell powder (ESP) and microwaved sewage sludge ash (MSSA) can be treated as alternative partial cement replacement in producing concrete. It may reduce the cost of the raw materials in concrete industry as well as minimize the effect on environmental pollution. The durability performances of concrete containing ESP and MSSA are tested against corrosion, acid attack, sulphate resistance and water absorption with different percentage of eggshell and different time of curing. The results show that microwaved sewage sludge ash (MSSA) and eggshell powder (ESP) are suitable as partial replacement to cement. The lowest rate of water absorption is concrete SE15 which is 3.96%, the lowest rate of corrosion also concrete SE15 which is 0.14% for acid attack and 0.04%